Perilaku penggunaan alat pelindung diri para pengunduh sarang burung walet: studi etnografi perilaku keselamatan kerja di Pantai Karangduwur Kabupaten Kebumen - Eka Denis Machfutra; Atik Triratnawati; Nida Ul Hasanat (Berita Kedokteran Masyarakat (BKM), 2017)
The use of personal protective equipment by swallow nest harvesters: an ethnographic study on safety behavior at Karangduwur BeachPurposeThe purpose of this study was to determine the behavior of traditional self-protection used by the swallow nest harvesters.MethodsThis research is a qualitative study with an ethnographic approach. The researchers participated in observing the behavior of bird swallow nest harvesters. The sample was chosen purposively based on the recommendation of the village head. Primary data were obtained through in-depth interviews and field observations. Secondary data were collected through document search on swiftlet nest download. The study was conducted from August-October 2016 with the instruments of interview guides, observation sheets and documents.ResultsDHarvesters used non-standard personal protective equipment. Downloaders tended to use traditional personal protective equipment, with the reasoning that using too much protection will interrupt the harvesting process. ConclusionThe use of personal protective equipment by harvesters is influenced by an interaction of factors between individuals and the environment and vice versa. The concerned agencies should pay close attention to the use of personal protective equipment used by Swallow's nest harvesters.